Randomized Controlled Trial of the Marriage Checkup: Depression Outcomes. (4th October 2019) - Gray, Tatiana D.; Hawrilenko, Matt; Cordova, James V.
Abstract : The association between relationship functioning and depressive symptoms is well established. This study examined the effects of the Marriage Checkup, a brief two‐session Assessment and Feedback relationship intervention, on depressive symptoms. Two hundred and nine married couples participated in the Marriage Checkup and were randomized into Treatment ( N  = 108) and Waitlist‐Control Conditions ( N  = 101). Compared to the control condition, intervention participants reported significant improvements in depressive symptoms ( d  = 0.55), with an even greater effect for those who were reporting more severe baseline depression symptoms ( d  = 0.67). These outcomes are comparable to those within long‐term individual psychotherapy, couple therapy, and pharmacology trials, making this the briefest intervention to date to demonstrate significant improvements in depressive symptoms. Clinical implications are discussed.